Tissue stages of Hepatozoon canis in naturally infected dogs from São Paulo State, Brazil - O'Dwyer, L. H.; Saito, M. E.; Hasegawa, M. Y.; Kohayagawa, A. (Springer, 2004)
A total of 222 dogs were examined by blood smear examination and Hepatozoon canis infection was detected in 13 dogs (5.9%). Five H. canis-infected dogs were necropsied to observe tissue stages in the organs. Fragments of spleen, liver, lungs, heart, kidneys, lymph nodes, bone marrow and skeletal muscles were used to made touch-impression smears. No macroscopic lesions were found in the organs. Two dogs had gamonts within polymorphonuclear cells and schizonts in various stages of development within the spleen and the bone marrow. Nevertheless, no mature meronts were found.